E-Wallet Models: An Appraisal of Shariah Related Issues - Asmadi Mohamed Naim; Azrul Azlan Iskandar Mirza; Abdul Rahman A. Shukor; Mohd Zakhiri Md. Nor; Nurul Aini Muhamed; Azuan Ahmad (Faculty of Sharia & Law UIN Syarif Hidayatullah Jakarta, 2024)
Vol 23, No 2